2018
DOI: 10.1007/s40093-018-0236-4
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of sorghum and sunflower in soils with amendment of sludge from industrial landfill

Abstract: Purpose The purpose of this work was to evaluate the impacts of the amendment of industrial landfill sludge (ILS) in two different soils with cultivation of sunflower and sorghum plants. Methods The plants grew in two types of soils (Typic Paleudult-TP, and Grossarenic Hapludult-GH) with different doses of ILS (0, 2, 5, 10, and 20 Mg ha −1). The evaluation of the pH, electrical conductivity, available concentrations of P, K, Ca, Mg, and Na, and the hydrolysis of FDA in the soils were tested. The height and dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Emami paper mill at Balasore produces about 100 tons of paper everyday utilizing waste papers and a considerable quantity of paper mill waste as byproduct in Balasore, Odisha. de Andrde et al (2019) has suggested economically and eco-friendly utilization of industrial landfill sludge by its amendment in soil instead of dumping in landfill due to high cost of landfills and loss of valuable plant nutrients essential for improved growth of sunflower and sorghum. Efforts were made earlier by different researchers for utilizing solid wastes of different paper mills either for producing porous bricks (Rajput et al 2012) or using as cheap adsorbent materials for removing oil (Kok 1983), grease (Lowe et al 1988), cellulose (Eifling and Ebbers 2006), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Emami paper mill at Balasore produces about 100 tons of paper everyday utilizing waste papers and a considerable quantity of paper mill waste as byproduct in Balasore, Odisha. de Andrde et al (2019) has suggested economically and eco-friendly utilization of industrial landfill sludge by its amendment in soil instead of dumping in landfill due to high cost of landfills and loss of valuable plant nutrients essential for improved growth of sunflower and sorghum. Efforts were made earlier by different researchers for utilizing solid wastes of different paper mills either for producing porous bricks (Rajput et al 2012) or using as cheap adsorbent materials for removing oil (Kok 1983), grease (Lowe et al 1988), cellulose (Eifling and Ebbers 2006), etc.…”
Section: Introductionmentioning
confidence: 99%
“…The germination percentage (%G) is the proportion, expressed as a percentage of germinated seeds to the total number of viable seeds (675) that were tested by using the formula of Bahira et al [17], Equation (1). The plant growth height was measured periodically.…”
Section: Germination Percentage and Growth Heightmentioning
confidence: 99%
“…This indicated that Cr is persistent in soil environments, and this is a source of concern. de Andrade et al [1] stated that the risk that could be associated with Cr(VI) amendment in soils may involve the chance of Cr persistence in soil and accumulation in plants that may eventually enter into the food chain. The concentrations derived were used to assess the transfer of Cr pollutants from soil to plants' portion using pollution indices, such as BF and TF, as monitoring tools for pollution effect on edible vegetables grown in Cr contaminated sites.…”
Section: Effect Of Chromium Concentration On Seed Germination and Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, industrial activities tend to generate a wide range of wastes, which have the potential to impact the ecosystems negatively and also lead to high-costs of treatment when such wastes are discharged to unprotected environments [1]. In developing countries, environmental laws on waste management and waste disposal are either non-existent or ineffective where they do exist [2].…”
Section: 0: Introductionmentioning
confidence: 99%